Changing Discursive Trends in the Online Review Genre : A Cross-Linguistic Study of BlaBlaCar - Hernández-López, María de la O., (Language and Linguistics E-Books Online, Collection 2024., 2025)
Around twenty years ago, with the digitisation of almost every facet of life, most businesses started including their own review system, so that their products could be rated and reviewed. This was the first wave of online reviews, called online consumer reviews (OCRs). The emergence of the smartphone and the proliferation of social media in the 2010s, however, resulted in a new ecosystem in which peers could share their assets, review other peers and be reviewed. This is the second wave of online reviews, or the emergence of online peer reviews (OPRs). This book explores the three differentiating discursive practices found in BlaBlaCar in Spanish and in English (emotive, relational and metacommunicative) as representative of this new wave. It demonstrates that OPRs have characteristics of their own, and proposes a new definition that captures the latest developments in online reviews in the context of peer collaboration.